The effects of foreign direct investment, trade, aid, remittances and tourism on welfare under terrorism and militancy - Olaniyi Evans; Ikechukwu Kelikume (International Journal of Management, Economics and Social Sciences (IJMESS), 2018)
The purpose of this study was to determine the effects of Foreign Direct Investment (FDI), trade, aid, remittances and tourism on welfare under terrorism and militancy. Using Nigeria as a case study for the period from 1980 to 2016, this study utilized autoregressive distributed lag (ARDL) bounds testing approach and the Cobb-Douglas production function. The empirical findings showed that, in the short-run, FDI, trade, aid, remittances and tourism had positive significant effects on welfare, even under terrorism and militancy. However, in the long run, only aid and remittances had significant effects while FDI, trade and tourism were insignificant. In other words, FDI, trade and tourist inflows were repressed as a result of the presence of terrorism and militancy in the long-run, meaning that they could not thrive in tensed and insecure environments. Surprisingly, despite the presence of militancy and terrorism, in the long-run, aid and remittances still had significant effects on welfare. The findings also showed that terrorism and militancy had significant negative effects on welfare both in the short and long run. In conclusion, terrorism and militancy not only undermined FDI, trade and tourism, but also led to a significant decline in welfare.
Keywords: D60; E27; H54; I31; 330; Foreign direct investment; trade; aid; remittances; tourism; terrorism; militancy